Multi‐Layer π‐Stacked Molecules as Efficient Thermally Activated Delayed Fluorescence Emitters - Wang, Xue‐Qi; Yang, Sheng‐Yi; Tian, Qi‐Sheng; Zhong, Cheng; Qu, Yang‐Kun; Yu, You‐Jun; Jiang, Zuo‐Quan; Liao, Liang‐Sheng (Angewandte Chemie International Edition, 2021)
Multi‐layer π‐stacked emitters based on spatially confined donor/acceptor/donor (D/A/D) patterns have been developed to achieve high‐efficiency thermally activated delayed fluorescence (TADF). In this case, dual donor moieties and a single acceptor moiety are introduced to form two three‐dimensional (3D) emitters, DM‐BD1 and DM‐BD2, which rely on spatial charge transfer (CT). Owing to the enforced face‐to‐face D/A/D pattern, effective CT interactions are realized, which lead to high photoluminescence quantum yields (PLQYs) of 94.2 % and 92.8 % for the two molecules, respectively. The resulting emitters exhibit small singlet–triplet energy splitting (ΔEST) and fast reverse intersystem crossing (RISC) processes. Maximum external quantum efficiencies (EQEs) of 28.0 % and 26.6 % were realized for devices based on DM‐BD1 and DM‐BD2, respectively, which are higher than those of their D/A‐type analogues. Multi‐Layer π‐stacked molecules are designed to realize efficient thermally activated delayed fluorescence. Spatially confined molecules with stereochemical structures are constructed in donor/acceptor/donor architectures with different conformations. Their organic light‐emitting diode (OLED) devices exhibit high external quantum efficiencies (EQEs) of 28.0 %/26.6 %, respectively.